2017
DOI: 10.1002/cphc.201700452
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Hydrochloride Structure in Solution Revealed by Three Chiroptical Methods

Abstract: Structure and flexibility of natural compounds determine their biological activity. In the present study, electronic circular dichroism (ECD), vibrational circular dichroism (VCD), and Raman optical activity (ROA) spectra of cocaine hydrochloride in aqueous solutions were measured and related to the structure with the aid of density functional theory (DFT) computations. Additional measurements in deuterated environment made assignment of vibrational bands easier. The results suggest that the prevalent cocaine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The chiroptical methods, specifically vibrational circular dichroism (VCD), electronic circular dichroism (ECD) and Raman optical activity (ROA), in combination with theoretical quantum chemical predictions can provide further 3D structural information on NPS in solution, which is crucial, e.g. for the understanding of their biological activity and toxicity [17][18][19]. The comparative analysis of experimental chiroptical properties and DFT calculations also allow the determination of the absolute configuration of individual separated enantiomers [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The chiroptical methods, specifically vibrational circular dichroism (VCD), electronic circular dichroism (ECD) and Raman optical activity (ROA), in combination with theoretical quantum chemical predictions can provide further 3D structural information on NPS in solution, which is crucial, e.g. for the understanding of their biological activity and toxicity [17][18][19]. The comparative analysis of experimental chiroptical properties and DFT calculations also allow the determination of the absolute configuration of individual separated enantiomers [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Like its natural analogue, butylone exhibits psychostimulant effects (eg, hyperlocomotion) and causes the increase of extracellular dopamine concentration. [15][16][17][18][19][20][21][22][23][24] The ab initio calculations allow a detailed interpretation of the experimental spectra of chiral molecules in solution. 9 Most studies 11-13 published thus far have been focused on racemic cathinones, and stereo-specific drug interactions have been demonstrated for amphetamines.…”
Section: Introductionmentioning
confidence: 99%
“…Chiroptical spectroscopy, specifically Raman optical activity, electronic circular dichroism (ECD), and vibrational circular dichroism (VCD), combined with quantum-chemical calculations are an efficient tool for the determination of the absolute configuration of separated enantiomers and their molecular stereochemistry. [15][16][17][18][19][20][21][22][23][24] The ab initio calculations allow a detailed interpretation of the experimental spectra of chiral molecules in solution. It has been demonstrated that the application of several independent chiroptical methods for the determination of the 3D structure of a chiral substance significantly increases the reliability of the obtained results.…”
Section: Introductionmentioning
confidence: 99%
“…There has been much effort put into the development of reliable and fast analytical methods for the identification and quantification of PDE-5 inhibitors in different types of real samples. [21][22][23][24][25][26][27][28] Optical rotatory dispersion, vibrational circular dichroism (VCD), and electronic circular dichroism (ECD) combined with IR and NMR spectroscopies were successfully used for the determination of the stereochemistry and 3D structure of all 4 stereoisomers of tadalafil in a solution. High-performance liquid chromatography, usually in tandem with mass spectrometry, is often considered to be the most important and commonly used method in pharmaceutical analysis, and the issue of PDE-5 inhibitors is not an exception.…”
Section: Introductionmentioning
confidence: 99%
“…20 Chiroptical spectroscopy, which is inherently sensitive to the 3D structure of chiral molecules, presents a powerful tool for the conformational analysis and determination of the absolute configuration. [21][22][23][24][25][26][27][28] Optical rotatory dispersion, vibrational circular dichroism (VCD), and electronic circular dichroism (ECD) combined with IR and NMR spectroscopies were successfully used for the determination of the stereochemistry and 3D structure of all 4 stereoisomers of tadalafil in a solution. 29 Another approach for the differentiation and quantitation of enantiomeric tadalafil isomers based on electrospray mass spectrometry was devised.…”
Section: Introductionmentioning
confidence: 99%